Consumption-based taxation at the business level: The Croatian experience - Helena Blažić; Nikša Nikolić; Mario Pečarić (The Journal of Entrepreneurial Finance and Business Ventures, 2003)
Croatia is the first country in the world to implement consumption-based direct taxation aimed at the individual as well as the business levels. Traditional corporate tax has been replaced by the so-called interest-adjusted profit tax, which encompasses the corporate as well as the non-corporate sector. This paper analyzes the efficiency of this tax in Croatia with regard to its neutrality as well as its cost-effectiveness. This tax can be regarded as neutral in terms of investment, finance, inflation and organizational form. But the imperfections of financial markets in Croatia still cause distortions between debt and equity capital as well as some distortions between the corporate and non-corporate sectors. The second efficiency aspect is identified as more doubtful, because of the relatively high tax expenditure of protective interest and incentive effects that have not been proven in practice.
Keywords: 650